Examining the Relationship Between Yoga Participation and Health. You Down, Dog? - (:unkn) unknown (My University, 2019)
The prevalence of debilitating chronic diseases, such as cardiovascular disease (CVD) and Alzheimer’s disease, are increasing in the United States. Inflammation, mitochondrial dysfunction, stress and depression are common pathologies associated with these chronic diseases. Many individuals engage in yoga because they believe it will improve their health. However, research examining the impact of yoga on markers of health associated with chronic diseases is limited and often reports conflicting results. Therefore, the purpose of this dissertation is to examine the relationship between yoga and inflammation, protein content of oxidative phosphorylation complexes, stress and depression, which may support the use of lifestyle interventions to promote health and wellbeing. The overall hypothesis of this dissertation is that yoga will be associated with improved markers of health; this will be tested through two separate studies. Study 1: Yoga and Health: A Cross Sectional Study used a cross-sectional study design to compare markers of health that are common pathologies for multiple, prevalent diseases between yoga participants and individuals who do not engage in yoga. Results support that yoga participants who engaged in yoga at least two times a week for the last six months have significantly improved perceived stress and symptoms of depression compared to non-yoga participants. Differences based on clinical cutoffs were also observed in a measure of systemic inflammation (erythrocyte sedimentation rate [ESR]). However, no differences were observed in C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α), nor adiponectin. Additionally, the Complex V protein content was not different between the groups, but this may be due to the age difference of the groups rather than differences in their yoga participation. Study 2: Adherence to and Changes in Physiologic and Psychologic Health during an 8-week Yoga Intervention: A Pilot Study was conducted to evaluate the feasibility and explore the impact of an 8-week yoga intervention on perceived stress, symptoms of depression, inflammation, and protein content of oxidative phosphorylation complexes to provide insight on the relationship between yoga and the pathology of CVD. While the majority (67%) of participants adhered to the protocol, our feasibility cutoff of ≥ 85%, created a priori, was not attained. Participants who completed the study (n = 8; 89%) observed reductions in levels of perceived stress (13.9%), depression symptoms (27%) and systemic inflammation (34%), and CRP (10%). An increase of 21% was observed in adiponectin. Contrary to the hypothesis TNF-α increased by 11% and there was a minimal change in the protein content of Complex V. Overall conclusion. Collectively, the findings from both studies support that participation in yoga can improve levels of perceived stress and symptoms of depression. Further, differences based on clinical cutoffs in the cross-sectional study and exploratory analyses from the pilot study show promising findings regarding the relationship between yoga and systemic inflammation. However, this work was not able to demonstrate a clear relationship between participation in yoga and inflammatory markers of CRP, TNF-α, adiponectin, nor mitochondrial protein content. These studies are the first to directly measure changes within the mitochondria in relation to yoga participation. Additionally, results support that yoga may be recommended as a lifestyle intervention to improve mental health outcomes and, with further research, possibly be used for physiologic variables.
Keywords: crp; inflammation; mental health; mitochondria; stress; Yoga